An Improved Impedance/Admittance Analysis Method Considering Collector Subsystem Transformation in Converter-Integrated Power Systems - Wang, Chenxuan; Wang, Zhen; Wu, Qiuwei; Xin, Huanhai (IEEE transactions on power systems, 2021)
To analyze oscillation phenomenon caused by the interaction between converters and an AC grid, the impedance/admittance analysis method is a popular solution, in which each electrical component is represented by an external impedance/admittance matrix and a lumped matrix is formed for stability analysis. However, for converter-integrated power systems considering typical collector subsystems (e.g., the radial and the ring collector subsystems in wind farms and PV stations), the impedance network reduction to form the lumped impedance/admittance matrix (LIM/LAM) becomes complicated particularly for a ring collector subsystem, which affects the efficiency of the oscillation analysis. To address this problem, this paper proposes a method that can transform a typical topology of collector subsystems into a pure-parallel topology so that lumped admittance matrix is much easier to be derived. Algorithm complexity analysis confirms its computational advantages. A fifty-converter system is used to verify the effectiveness of the proposed method.